EZ430-chronos watch as a wireless health monitoring device - Mohd. Nordin, I. N. A. (Springer Berlin Heidelberg, 2011)
The paper describes a wireless health monitoring system, developed in LabVIEW, which is able to transmit and receive a patient's body signal wirelessly to an eZ430- Chronossport watch.Patient's vital body signal such as heart rate and percentage of oxygen saturation will be wirelessly transmitted to a programmable eZ430-Chronos watch to ease patient monitoring. The watch, used as a monitoring device will be worn by the doctor or any other individuals who is responsible in monitoring a patient's condition (i.e.nurse or any of the patient's family members). The system enables the user to be alerted immediately should any abnormalities occur to a monitored patient and he/she can be attended instantly. This would improve patient monitoring system remotely within the wireless protocol given.